Development of Supplementary Textbook Based 0n the Local Wisdom of Bangkalan - Atika Maulidina Hs; Agung Setyawan (Universitas Pendidikan Indonesia (UPI), 2022)
One effort to make it easier for students to understand thematic material is to include the content of their own local wisdom in learning. Unfortunately, at this time, there are no accompanying textbooks that contain local wisdom content. The purpose of this research and development is to produce a complementary textbook product based on Bangkalan local wisdom that is valid, effective, and practical to improve students' cognitive outcomes. This research procedure uses a 10-step design from Borg and Gall. The results of expert validation of the developed textbooks were 86%, while the validation from practitioners was 93%, each indicating that the products developed were classified as very valid and feasible to use. The effectiveness of the product is seen from the classical learning outcomes that is equal to 100%, indicating complete and effective learning. The practicality of the product is assessed from the average value of the student and teacher questionnaire responses, which is 93% and the observation of the implementation of teacher and student learning with the results of 94%, each of which shows very practical criteria. The results of the study indicate that the companion textbook product based on Bangkalan local wisdom that was developed is very valid, effective, and practical so that it is suitable for use in classroom learning.